Salt tolerance of spinach as related to seasonal climate - S. Ors; D.L. Suarez (Horticultural Science, 2016)
Three sets of experiments with spinach (Spinacia oleracea L., cv. Racoon) were conducted under saline water irrigation during different time periods between December 7, 2012-June 15, 2013 to understand the impact of increased temperature on salt tolerance in cool season crops. The first experiment consisted of 4 different salinity levels: 0, 4, 7, 9 dS/m and the two subsequent experiments each had 6 different levels of saline water: 0, 4, 7, 9, 12, and 15 dS/m. Irrigation water salinity up to 9 dS/m did not cause any yield loss in spinach during the first set of experiments, indicating that this cultivar is considerably more salt tolerant than spinach varieties reported in the literature. Severe salinity caused yield loss and decreased all gas exchange and vegetative parameters. It was found that spinach was considerably more salt tolerant under cool season late winter conditions than under warmer climatic conditions. The increase in temperature between experiment I and II was 12.5°C while the relative yields decreased by 31% at the same salinity treatment (9 dS/m).